Analysis of Discipline, Effectiveness and Barriers to Online Learning During the Pandemic Reviewed From The Views of Students - Aulya, Nanda; Karmila, Nur; Wulandari, Rika (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research article analyzes the effectiveness and obstacles in learning during a pandemic. The method used by researchers is a qualitative approach method. This is based on the results obtained from the data that the average discipline is not good, and the effectiveness of learning is that many students do not like online learning, as well as obstacles when online learning takes place, such as obstacles in accessing the internet network. The survey used by this researcher is a questionnaire consisting of 9 questions. The subjects of this study were 20 students in class XII MAN 2 Jambi City with a total of 3 classes who had undergone online learning. Of the three classes, there were class XII IIS 1 (9 students), XII IIS 4 (4 students), and XII IIK 3 (7 students) as samples. The data collection technique uses a questionnaire via a Google form given to students via a questionnaire.